Analysis of the Effect of Work Meaning and Work Totality on Work-Life Balance of Female Workers in Capital Cities in Indonesia - Ratnawita Ratnawita; Ade Risna Sari; KMT Lasmiatun; Fatimah Malini Lubis; Abdurohim (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This research aims to elucidate the impact of the entirety of employment and the significance of employment on the equilibrium between work and personal life in female employees. The participants in this study consist of 300 married, full-time female employees in various major cities in Indonesia. For this investigation, a quantitative methodology is used. Through the usage of the Google Form link, data is indirectly collected online. Through confirmatory factor analysis (CFA), each measuring device's concept validity is examined using the Lisrel 8.70. Multiple regression analysis methods are used with SPSS's assistance to test the study hypothesis. The purposive sampling method makes use of non-probability sampling. The study's results show that the combined impact of work significance (genuineness, self-efficacy, self-worth, purpose, belongingness, transcendence, culture, and interpersonal understanding) and work entirety (enthusiasm, dedication, and flexibility) on work-life balance exceeds 50%. Commitment, sincerity, and self-efficacy are the factors that have a substantial impact on work-life balance.